Genetic prevalence of antifungal resistance gene in cancer patients with Oropharyngeal Candidiasis from Iraq. (Baghdad Science Journal, 2024)
As the population of immunocompromised patients grew, yeast infections became more common. There has been a significant rate of morbidity and mortality among patients with Candidiasis demonstrating increased resistance to antifungal medications. The main aim of this study was to determine the virulence gene of Candida albicans, evaluate antifungals used for Candidiasis, and biofilm formation, which is isolated from the mouth of individuals in the Baghdad Governorate From 1st October 2022 to 28th February 2023. This study included 120 oral swabs collected from people who had oral candidiasis, with an age group between10-65 including both Genders. The results obtained showed that the candidiasis frequency was more prevalent in males between the age group of 11-20 years. These results showed a statistically significant increase in the prevalence of ERG11 virulence gene among the biofilm-forming C. albicans fungus compared to other isolates with a significant difference (P = 0.863). Also, the study showed significant resistance of C. albicans to the antifungals fluconazole, itraconazole and fluconazole with the ability to form a biofilm. The present study also highlighted an elevated prevalence of the ERG11 gene in C. albicans and a strong association between the formation of biofilms and the presence of virulence gene was noted. Candidiasis is one of the fungal infections that are more prevalent among patients, and the virulence factor biofilm has an important role in increasing the pathogenicity of the fungus.